2019
DOI: 10.1021/acsami.9b06162
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation of Pd(II) on Pyridine-Functionalized Graphene Oxide Prepared by Radiation-Induced Simultaneous Grafting Polymerization and Reduction

Abstract: The recovery of precious metals like palladium (Pd) from secondary resources has enormous economic benefits and is in favor of resource reuse. In this work, we prepared a high efficiency pyridine-functionalized reduced graphene oxide (rGO) adsorbent for selective separation of Pd­(II) from simulated electronic waste leachate, by one-pot γ-ray radiation-induced simultaneous grafting polymerization (RIGP) of 4-vinylpyridine (4VP) from graphene oxide (GO) and reduction of GO. The poly­(4-vinylpyridine)-grafted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…This allows for a variety of applications [144]. Over the last 5 years, the major applications remain in accordance to societal needs with the development of: adsorbents for depollution (removal of toxic metals [144][145][146][147][148][149][150][151][152], ammonia/ammonium species [153,154], atmospheric CO 2 [155]); exchange membranes for fuel cell (anion [156,157] and proton [158,159], batteries or super capacitors [116]; functional fibers other than adsorbent applications (flame-retardant [160], antistatic and antibacterial [161] properties); and numerous applications are emerging in the field of renewable energies [162].…”
Section: Radiation-induced Grafting Of Solid Polymersmentioning
confidence: 99%
“…This allows for a variety of applications [144]. Over the last 5 years, the major applications remain in accordance to societal needs with the development of: adsorbents for depollution (removal of toxic metals [144][145][146][147][148][149][150][151][152], ammonia/ammonium species [153,154], atmospheric CO 2 [155]); exchange membranes for fuel cell (anion [156,157] and proton [158,159], batteries or super capacitors [116]; functional fibers other than adsorbent applications (flame-retardant [160], antistatic and antibacterial [161] properties); and numerous applications are emerging in the field of renewable energies [162].…”
Section: Radiation-induced Grafting Of Solid Polymersmentioning
confidence: 99%
“…Hybrid materials have also been used to recover precious metals (e.g., Pd, Au, Pt). Previous studies have reported a high-recovery material based on a polymer consisting of thiocarbonyl groups for metal coordination and amino groups for hydrophilicity . Gelation occurred through self-assembly between the thiocarbonyl groups and metal ions, precipitating the self-assembled polymer–metal complexes, which were then separated by filtration (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…58 Post-synthesis COF functionalization by grafting is an appealing alternative synthetic strategy, 52,[59][60][61] among which radiation-induced grafting polymerization represents a typical and mature method of post-synthesis with a long history. [62][63][64][65][66][67][68][69] Compared with chemical initiation methods, g-ray radiation-induced grafting possesses advantages of environmentally green, effective, energy-efficient, and operationally simple for functional modification of substrates. grays are also penetrative enough to ensure the homogeneity of the grafting reaction and, thus, the excellent mechanical properties of the COFs allow continuous and stable operation of the column experiments by maintaining the intrinsic structure of the…”
mentioning
confidence: 99%